Avaliação do caranguejo-uçá, Ucides cordatus (ocypodidae) como potencial bioindicador de contaminação por metal nos manguezais da costa paraense - RODRIGUES, Deliane Hillary do Amaral (2022)
The crab, Ucides cordatus, is a natural resource heavily exploited in the Amazon region and has been used as an important bioindicator of heavy metal contamination in Brazil. In the present study, we quantified the concentration and bioaccumulation of five metals (Cd, Cr, Cu, Mn, and Pb) in U. cordatus, in order to evaluate the species as a potential bioindicator of metal contamination in the mangrove ecosystem of the Pará coast. Three specimens were captured per sampling subarea (n = 3) of mangrove in the cities of Bragança (considered a preserved area) and Viseu (considered an anthropized area), both in the state of Pará, as well as sediment samples. Metal concentrations in biotic and abiotic samples were quantified by Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES), with the subsequent estimation of the Bioaccumulation Factor and multilevel analysis for the metals evaluated. The results obtained in the sediment showed that the Mn detected in the anthropized area was three times higher than in the preserved area. The metals Cu and Cr presented significant differences and the highest values for the anthropized area. In the crab musculature, Cu concentrations of samples collected in the anthropized area were higher than in the crabs from the preserved area. Pb was the second metal showing a higher value in the specimens collected from the preserved area than in the anthropized area. In conclusion, the crab presents itself as an excellent bioindicator species of the state of conservation of mangrove areas in the Amazon coast, presenting authentic parameters to categorize the level of contamination of the areas studied here.